Challenges of Indigenous Students in Overcoming Difficulties in Learning Algebra: A Problematic Perspective of Ethnomathematical - Rani Darmayanti; Dwi Priyo Utomo; Kamilia Rahmah; M. Ruskhan Fauza; Alfi Rachma Nisfi Laila; Choirudin Choirudin (STAI Hubbulwathan Duri, 2023)
This study aims to explain the position of ethnomathematical learning in a space that involves the challenges and problems of indigenous students in overcoming difficulties in learning algebraic material with qualitative descriptive research. Information was collected by finding out the sample from this study, which was conducted using a multi-stage sampling technique. The theme chosen was one grade VII student and one grade VIII student at the Pasuruan ALC Foundation, where both students were indigenous students with problems with algebra material. Ethnomathematics learning with a cultural context at the historical site of Candi Jawi is expected to overcome the difficulties of learning pure mathematics for indigenous students at the Assyfa Learning Center Foundation in Pasuruan.